Logitech diNovo Edge, Mac edition livin' on the edge. - Aguilera, Ray.
The diNovo Edge Mac Edition features all the Mac-specific keys.
Keywords: Keyboards (Elecronics); Wireless keyboard; Wireless bluetooth keyboard